Efektivitas Penerapan Hukum Positif terhadap Pembalakan Liar Atas Hutan Di Kabupaten Asmat - Alfian, Akhmad (Ridwan Institute, 2021)
Asmat regency has a mushy soil system, and nearly all of Asmat's buildings are constructed on swamp. As a result, wood has become the most important infrastructure necessity in Asmat, and people are harvesting wood from the forest to meet this need. The regulation on timber retrieval in Asmat will be governed in Perbup Asmat No 8 Tahun 2019, which was published with local wisdom in mind. This is an observational legal study, in which data was gathered through interviews and literature reviews. The data analysis method in this study was done qualitatively. Following that, the data was systematically analyzed in order to gain clarification on the topics to be addressed. The Asmat Local Government's authority to administer forests is immediately taken away with the enactment of Law 23 of 2014. As a result, Perbup Asmat No. 8 Year 2019 no longer applies as a guide to the rules for taking timber and forest products in Asmat. Since the vast Asmat forest, which is divided by a massive river, is only protected by two government employees, the province's authority over forest management has weakened forest surveillance in Asmat. Positive logging legislation is becoming more difficult to implement. If the implementation of positive law is not applied, the current laws will undoubtedly be broken. However, if the positive laws are applied, the group would be unable to take wood from the trees, resulting in the Asmat people's economic demise. This is due to the fact that wood has become the Asmat people's primary need.